Albrecht Dürer and the depiction of cultural differences in Renaissance Europe - Madar, Heather (Routledge Critical Junctures in Global Early Modernities, 2023)
1. From Saracen to Turk: Dürer and the Origins of Ottoman Imagery in German Renaissance Art -- 2. Ottoman, Mamluk and Roman: Dress and Identity in Dürer's Art After 1495 -- 3. Ottomans as Ottomans: Portraiture, Genre and Polemical Imagery -- 4. Black Ottomans and Black Mamluks: Racial Difference in Dürer's Depictions of Muslim Figures -- 5. Katharina and Portrait of a Young Man: Black Presence in Renaissance Europe -- 6. Conclusion: Dürer's Theories of Human Difference -- Works Cited -- Index.